Cartera de crédito vencida de la cooperativa de ahorro y crédito el cafetal - Rizo Sánchez, Antonia Lisbeth (2018)
The savings and credit cooperative el cafetal, is an institution that is responsible for granting credit, is constituted by the beneficiaries that has the objective of promoting the saving and promoting the family economy. Definition of cooperatives art.34.- Are cooperatives, economic organizations solidarity, constituted as private law societies, with social purpose and without for profit, which integrate contributions in the economy of the country. (Eco. Milton Maya). The capital generated by the credit union and the coffee plantation comes from the contributions from members, savings account, loans at reasonable interest which they are primarily generated for peasants and small merchants. The present case lies in the incidence of agricultural credits in the portfolio expired of the Cooperative of Savings and Credit the coffee plantation of the city of Babahoyo, this it occurs when agricultural credit is approved without an adequate analysis that is why the Past due portfolio has been increasing over the years. For this reason the greatest part of its non-performing portfolio is in the short-cycle agricultural credits, corn, soybeans, rice, because the partner often can not pay his quota in time stipulated in the contract. The present work is framed in the research subline "Management of the accounting information "which is similar to the problem that is located in the coffee cooperative, verifying what is stipulated in the research lines from the school of accounting, auditing and finance.